How is modern bedside teaching structured? A video analysis of learning content, social and spatial structures - Anna-Lena Blaschke; Hannah P. K. Rubisch; Ann-Kathrin Schindler; Pascal O. Berberat; Martin Gartmeier (BMC Medical Education, 2022)
Abstract Background Bedside teaching (BST) is an essential and traditional clinical teaching format. It has been subject to various impediments and has transformed over time. Besides a decrease in bedside time, there has also been a didactic diversification. In order to use time at the bedside effectively and understand the current design of BST, we here offer an evidence-based insight into how BST is practiced. This may serve as a basis for a refinement of its didactic design. Methods In the current study, we investigate the interrelationships between learning content and the social as well as spatial structures of BST. To this end, we have empirically analysed almost 80 hours of video material from a total of 36 BST sessions with good interrater reliability. Results BST lasted on average 125 min, most of which was spent in plenary and less than a third of the time at the patient’s bedside. History taking was primarily practiced at the bedside while case presentations, clinical reasoning and theoretical knowledge were largely taught away from the patient. Clinical examination took place to a similar extent in the patient’s room and in the theory room. Conclusions Even though the filmed BSTs are not purely “bedside”, the teaching format investigated here is a typical example of undergraduate medical education. In order to maximize the teaching time available, a suitable learning space should be provided in addition to the bedside. Moreover, the clinical examination should be revised in its general sequence prior to the BST, and conscious decisions should be made regarding the social structure so as to optimize the potential of small groups and plenary sessions.